PELATIHAN PEMBUATAN JERAMI PADI DIFERMENTASI UNTUK PAKAN DOMBA DI KABUPATEN GARUT - Diky Ramdani; Ken Ratu Gharizah Alhuur; Farah Lasti Utami; Kevin Immanuel; Aulia Sabrina Faisal Bermani; Ratu Asyfa; Zalfa Hasna Nadhira; Diny Putri Istiqomah; Muhammad Farhan Ardi Wiguna; Muhammad Arkan Lamiday (Farmers: Journal of Community Services, 2022)
Kuliah Kerja Nyata Program (KKN) on the manufacture of fermented paddy straw for sheep was carried out using a mixed method, namely through webinar media and conducting direct surveys to the field. The place where fermented paddy straws are made at Paddy Farm which is located in Panerusan Village, Tanjung Kemuning Village, Tarogong Kaler District, Garut Regency. As for the webinar, it will be carried out through the media zoom which will be held on August 7, 2021, with a total committee of eight people. Indonesia is one of the countries that has a large area of rice fields, so the availability of paddy straw resources is also abundant. This can be exploited by using paddy straw as an alternative material for sheep feed. However, paddy straw has low palatability and nutrient quality. Fermentation will greatly help to improve the quality and palatability of paddy straw. The procedure for making fermented paddy straw is delivered through webinars and videos uploaded on the Youtube application. Sheep farmers can see the procedure for making fermented paddy straw through the media. Key Words: Fermentation, Paddy straws, Farmers, Sheep.